Proton beam writing: World experience and prospectives in Ukraine - H. Ye. Polozhii; A. G. Ponomarev; S. V. Kolinko; V. A. Rebrov; R. O. Shulipa; O. M. Kalinkevich; O. V. Kalinkevich (Ядерна фізика та енергетика)
Proton beam writing is a promising lithography method that is being developed in many countries. This method has significant advantages over other lithography methods, amongst all, there is the absence of the need for prefabricated pattern masks and a high aspect ratio of fabricated structures. Numerous publications demonstrate prospective applications of proton beam writing in different fields related to micro- and nanostructures fabrication. Proton beam writing may be used both for nanoelectronics and three-dimensional microstructures with a high aspect ratio. Work on proton beam writing technology is being conducted at the Institute of Applied Physics of the National Academy of Sciences of Ukraine. Last years there were introduced vector proton beam writing method, an electrostatic blanker system for proton beam distortion, and experiments on proton beam writing on chitosan films were conducted, including the films covered with thin films of metals and metal compounds.